ANALOGUE SANDBOX MODELLING OF THRUST FAULT DEVELOPMENT - Alfa Furqan, Terry
Understanding the kinematic evolution of the hanging wall block during the thrust faults formation within fold-and-thrust belts (FTB) is essential for optimizing hydrocarbon exploration activities and disaster mitigation in FTB regions. This study employs Particle Image Velocimetry (PIV) analysis on sandbox analog model to observe how the kinematic evolution of the hanging wall block during the development of thrust faults. This study provides insights regarding thrust fault formation, which can help to estimate the sequence of thrust fault development in hydrocarbon migration and predict active thrust fault segments within FTB. Experimental results indicate that thrust faults develop through three distinct phases. In the first phase, horizontal strain accumulation initiates the nucleation of thrust faults, reflecting strain hardening. This is followed by the second phase, characterized by the propagation of the thrust fault plane accompanied by a significant increase in displacement magnitude, which reflects strain weakening. The final phase involves the translation of the hanging wall along the established fault plane with a relatively constant displacement magnitude. Thrust fault imbrication is formed through the repetition of these three phases, with intersections between the first and third phases. Several architectural parameters of the FTB influences the kinematic evolution the hanging wall. Increased slope angles and higher basal friction coefficients impede material movement, thereby steepening the topographic slope and increasing the total slip of thrust faults. Additionally, increasing the thickness of sand layers enlarges the geometry of thrust faults and raises the strain required for their formation. Lateral variations in the geometry of the orogenic zone controls the distribution of hanging wall kinematics, resulting in imbricated thrust faults that align with the geometry of the orogenic zone. Basement deformation within sandy layers leads to slower and more dispersed hanging wall kinematics compared to the rigid blocks, resulting in shorter thrust displacements within sandy layers.